Misuse of topical corticosteroids on facial skin - Fasih, Sadaf; Arif, Asad Bilal; Amar, Ali; Haque, Mazhar ul; Hameed, Farheen; Iqbal, Jawed (Pakistan Journal of Physiology, 2020)
Background: Topical corticosteroids are being misused all over the world due to their easy availability leading to various adverse-affects. This study was conducted to assess the magnitude of the problem and side-effects of topical corticosteroids application over the face. Methodology: This is a hospital based cross-sectional descriptive study was conducted at Shahida Islam Teaching Hospital and Medical Complex, Lodhran, over a period of 6 months from Jun to Nov 2018. The inclusion and exclusion criterion were defined and patients were questioned on a structurally designed preformed questionnaire and examined clinically. The data was processed using SPSS-20. Results: A total of 220 patients were included in the study, out of which 160 patients were females. Age of the patients ranged from 8 to 40 years. Most of the patients (84, 38.2%) applied steroid only for fairness while others used it for the treatment of acne, melasma, tinea and other dermatoses. Most of the patients (168, 78%) used steroids on the advice of non-doctors. Multiple adverse effects like erythema, burning, itching, telangiectasia, hypertrichosis, tinea incognito, photosensitivity and skin atrophy were noted. Among those who developed side effects, 98 (44.5%) patients developed Topical Steroid Dependent Face (TSDF). Conclusion: Topical corticosteroids are misused most commonly for fairness and other skin conditions by doctors and non-doctors without proper consultation by dermatologists. Stronger regulations and more stringent policies for the manufacture and sale of over the counter drugs are recommended. Public awareness can help to address the problem. Pak J Physiol 2020;16(3):11–3